2019
DOI: 10.48550/arxiv.1911.08134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protecting RESTful IoT Devices from Battery Exhaustion DoS Attacks

Abstract: Many IoT use cases involve constrained batterypowered devices offering services in a RESTful manner to their communication partners. Such services may involve, e.g., costly computations or actuator/sensor usage, which may have significant influence on the power consumption of the service Providers. Remote attackers may excessively use those services in order to exhaust the Providers' batteries, which is a form of a Denial of Service (DoS) attack. Previous work proposed solutions based on lightweight symmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The basic idea in all solutions that belong to this category is to detect anomalies in behavior such as, sending too many RPL control messages in a given time period. Examples of approaches that belong to this category are [63] and [64]. Authentication approaches utilize lightweight authentication schemes using either symmetric or asymmetric keys to identify requests from legitimate nodes.…”
Section: Dos Attacks Countermeasuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic idea in all solutions that belong to this category is to detect anomalies in behavior such as, sending too many RPL control messages in a given time period. Examples of approaches that belong to this category are [63] and [64]. Authentication approaches utilize lightweight authentication schemes using either symmetric or asymmetric keys to identify requests from legitimate nodes.…”
Section: Dos Attacks Countermeasuresmentioning
confidence: 99%
“…The impact of these attacks on edge IoT nodes was demonstrated by Ioulianou et al [63] and their simulations showed that node activity has increased from 35% during normal operation to 50% during an attack for affected nodes. However, one of the limitations of most of the these studies is that their simulations, if any, are small scale simulations with simplistic scenarios to show the significant impact on battery drain [47], [63], [64].…”
Section: Dos Attacks Countermeasuresmentioning
confidence: 99%
“…Rate Limiting solutions [106] articles [54]. For instance, malware inserted into vendor websites or devices can "trojanize" devices before the devices leave the supply chain.…”
Section: E-iot Devices Layer: Attacks and Vulnerabilitiesmentioning
confidence: 99%
“…In situations where devices may be homogeneous, defenses against battery exhaustion attacks can be based on comparing these devices to create a realistic baseline and find anomalies that may be effective in wireless sensors and interfaces [105]. Finally, work by Hristozov et al using rate limiting approaches to defend against battery exhaustion attacks reported to be successful for devices supporting RESTful services [106].…”
Section: Battery Exhaustion Defensesmentioning
confidence: 99%
“…Rate limiting: Authors in [122] proposed rate-limiting to prevent such attack. However, identifying such a single threshold for devices using network data is challenging.…”
Section: Sleep Deprivation Attackmentioning
confidence: 99%